Local Versus Long‐Range Diffusion Effects of Photoexcited States on Radiative Recombination in Organic–Inorganic Lead Halide Perovskites. Issue 9 (14th July 2015) - Vrućinić, Milan; Matthiesen, Clemens; Sadhanala, Aditya; Divitini, Giorgio; Cacovich, Stefania; Dutton, Sian E.; Ducati, Caterina; Atatüre, Mete; Snaith, Henry; Friend, Richard H.; Sirringhaus, Henning; Deschler, Felix
<x xml:space="preserve">Abstract</x> Radiative recombination in thin films of the archetypical, high‐performing perovskites CH3NH3PbBr3 and CH3NH3PbI3 shows localized regions of increased emission with dimensions ≈500 nm. Maps of the spectral emission line shape show narrower emission lines in high emission regions, which can be attributed to increased order. Excited states do not diffuse out of high emission regions before they decay, but are decoupled from nearby regions, either by slow diffusion rates or energetic barriers.